Finding Theodore and Brina. - White, Terri-Ann (Curtin University, 2000)
The form I have chosen for this dissertation is fiction-of a certain kind- that incorporates historical detail, family history, and popular mythology of the Western Australian community. Through the details of family and social history, I aim to tell another version of settlement of Perth from the mid-nineteenth century to the present. This story belongs to my family, starting with great-grandparents who travelled from London to Australia in the 185Os: one as a convict, one a free settler; both were Jewish, and the convict was Polish.The writing is textured with forgotten voices, is self-reflexive, and tackles the paradoxes involved in telling stories from within the family I belong to, one that resists telling its own stories because of shame and the lack of an authoritative, or socially given, voice. From family history to social history, my interest is in the material that sits on the margins: the unspoken and generally unwritten histories of people on the edges of this society. This material, which is not recorded or spoken, nonetheless "speaks" a shame that shapes the ever-developing identity of a family and a community.The work is informed by feminist ideas about voice and the hierarchy which licenses select people in our society to speak. Relying on the varied materials that sit between historical writing and personal memories, it follows evidence, both written and oral, recognising how malleable memory can be. One of my purposes is to explore ideas about memory, from the individual act of memory to its transmutation into collective memory-to recover, recuperate, and explore what is involved in forgetting and remembering, and do this through a layering of stories, of voices, of form.